2011
DOI: 10.1088/0957-0233/22/8/085203
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal noise and drift in fiber optic distributed temperature sensing

Abstract: Distributed temperature sensing (DTS) allows for simultaneous measurement at many remote locations along an optical fiber probe and is a valuable tool in a broad range of applications, such as downhole oil production, dike structural monitoring or fire protection. The specific requirements on spatial, temporal and temperature resolution and on absolute measurement uncertainty vary with the applications. We investigate the spatio-temporal noise and drift properties of two exemplary Raman backscatter DTS systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Figure 4 shows the results. The average RMSE of the points before the splice, from 326 m to 338 m, was 0.080 K. The RMSE of the points after the splice, from 1,224 m to 1,236 m, was 0.10 K. The overall RMSE of the bath temperature, based on the average of all 15 points, was 0.060 K and the bias was 0.003 K. Under laboratory circumstances, Voigt et al [ 28 ] found a standard deviation that was very close to the factory supplied specification of 0.07 K for measurement integration times of 60 s at 1 km. Here, we find slightly higher values than specified by the factory but this may be partially due to the fact that the accuracy of the TSic 506 measurement was around 0.04 K. We may conclude that also under these field conditions, one can obtain temperature measurements with accuracy close to the nominal one after careful calibration.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the results. The average RMSE of the points before the splice, from 326 m to 338 m, was 0.080 K. The RMSE of the points after the splice, from 1,224 m to 1,236 m, was 0.10 K. The overall RMSE of the bath temperature, based on the average of all 15 points, was 0.060 K and the bias was 0.003 K. Under laboratory circumstances, Voigt et al [ 28 ] found a standard deviation that was very close to the factory supplied specification of 0.07 K for measurement integration times of 60 s at 1 km. Here, we find slightly higher values than specified by the factory but this may be partially due to the fact that the accuracy of the TSic 506 measurement was around 0.04 K. We may conclude that also under these field conditions, one can obtain temperature measurements with accuracy close to the nominal one after careful calibration.…”
Section: Resultsmentioning
confidence: 99%
“…This example 502 suggests that while good results can be obtained with remote weather stations, in-situ 503 measurements may provide better results. Another likely explanation for the error in the 504 modeled stream temperatures at Ninemile Creek is the systematic, high frequency noise that is 505 inherent to fiber optic DTS data collected over short integration times and distances (DC3; 506 Briggs et al, 2012;Voigt et al, 2011). Discrepancies exist between the measured temperatures, 507 which include this high frequency noise, and the modeled temperatures.…”
Section: Model Evaluation Across Contrasting Field Sites 428mentioning
confidence: 99%
“…The results of this study demonstrate that temperature measurements with an accuracy of approximately 0.1 • C can be obtained by fiber optic DTS. A more accurate temperature precision can be obtained with integration, either over longer time or greater lengths of cable (Voigt et al, 2011). However, this would be at the expense of measuring finer spatial scales or more rapid temporal changes.…”
Section: Discussionmentioning
confidence: 99%